Spectrophotometric Determination of Cobalt(II) after Separation by Adsorption of its 1-Diethylamino-2-Propanol Complex on Microcrystalline Naphthalene. - RATHORE, SANJEETA; KUMAR ARORA, SURENDRA; DUGGAL, RAKESH; SHARMA., K.K. (Asian Journal of Chemistry, 2010)
The spectrophotometric determination of trace amount of cobalt(II) with 1-diethylamino-2-propanol is described after the adsorption of cobalt(II) complex on microcrystalline naphthalene. This complex is stable in naphthalene dimethylformamide solution. The absorption obeyed Beer's law over the concentration range of 10–100 μg of cobalt(II). The molar absorptivity was 1.19 x 104 1 mol–1 cm–1, the sensitivity being 0.007 μg cm–2for the absorbance of 0.001.